Trust and lament in the macalot psalms (Psalms 120-134) - Viviers, Hennie (Old Testament essays, 1992)
All macalot psalms with the combined motifs of trust and lament are investigated. Strong emphasis is placed on the poetics of these psalms, which is indispensable in determining theme, unity and the function of motifs. The motif of trust is dominant over that of lament. Lament always presupposes trust. The original unity of each poem speaks against a gradual expansion of a 'kernel' motif into the final poem. The motifs of trust and lament were probably both active during the compositional phase of the poems. The importance of trust in each ma'^^lot psalm is also confirmed by the wider context, the macalot collection, which is a (post-exilic) 'book' of trust.